Development of Visualization Metaphors for Monitoring Student Engagement in Distance Learning Environments - Oliveira, Pamella L. S. de; Rodrigues, Rodrigo L.; Maciel, Alexandre M. A. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2023: Anais do XXXIV Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/sbie.2023.234819, 2023)
Given the low percentage of graduates in Distance Education courses, the need to visualize student data is perceived, as it makes it easier to monitor educational phenomena, such as engagement. The literature shows some gaps, such as the absence of analysis of visualization metaphors. This work aims to develop visualizations with educational data using the stages of understanding the problem, construction, and evaluation. The results show the choice of five visualization metaphors to present engagement variables. In addition, the evaluation results point to the absence of a tool for monitoring and the importance of viewing groups.